Analisis Rasio Likuiditas, Solvabilitas, dan Profitabilitas Untuk Menilai Kinerja Keuangan Pada PT Telkom Indonesia Periode 2022-2024 - Shintia Kalimayanti; Shiva Kurnia Putri; Amanda Ramadhani; Melsandi i (Pascasarjana Universitas Sultan Ageng Tirtayas, 2025)
This study aims to evaluate the financial performance of PT Telkom Indonesia (Persero) Tbk, listed on the Indonesia Stock Exchange, during the period 2022–2024 using financial ratio analysis. This study uses a descriptive quantitative approach based on secondary informasi obtained from the companys annual financial reports. The analysis focuses on liquidity, solvency, and profitability ratios. The results indicate that the companys liquidity performance remains below industry benchmarks, indicating challenges in meeting short- term financial obligations. Conversely, the company exhibits a relatively stable and well- managed capital structure. From a profitability perspective, operating profit is satisfactory; however, returns on aktivas, equity, and investments have not yet reached maksimal levels. Overall, the financial performance of PT Telkom Indonesia (Persero) Tbk can be considered quite positive, although improvements in liquidity management and aktiva utilization efficiency are still needed.